(untitled) (Research Journal Tahqeeqat, 2025)
An analysis of romantic elements in the Urdu fiction of Khyber Pakhtunkhwa shows that the motivation for the romantic elements found in the Urdu fiction writers of Khyber Pakhtunkhwa is their own region. The fiction writers of Khyber Pakhtunkhwa have well depicted the environment of this region in their fiction. The romantic elements found in the Urdu fiction of Khyber Pakhtunkhwa are of different types. Some fiction writers have depicted the rural environment, while others have made the natural environment, rivers, mountains and waterfalls the subject of discussion. Each fiction writer has adopted a different romantic style of describing life and its attitudes. Overall, the fiction writers of Khyber Pakhtunkhwa have depicted the romantic trend along with literary trends in a good way. The region of Khaiyber Pakhtunkhwa is very fertile in terms of literature. Urdu fiction has been greatly cultivated in it. The names of the writers of the Khyber Pakhtunkhwa period are of great importance in the context of the romantic style in Urdu fiction. The writers of the fiction who experimented in this genre should always be remembered in Urdu literature.